Особенности выбора батарей конденсаторов в электрических сетях с источниками интергармоник - Саенко, Ю.Л.; Бараненко, Т.К.; Калюжный, Д.Н. (Електротехніка і електромеханіка, 2017)
Разработана методика выбора батарей конденсаторов, применяемых как в качестве компенсаторов реактивной
мощности при наличии источников интергармоник, так и в составе фильтров высших гармоник и интергармоник.
Получены выражения для проверки отсутствия недопустимых перегрузок батарей конденсаторов по напряжению и
по току при наличии в кривой напряжения (тока), наряду с высшими гармониками, дискретного спектра интергармоник. Обоснована целесообразность упрощенного учета изменения напряжения на зажимах батарей конденсаторов
фильтров высших гармоник и интергармоник за счет наличия реактора в составе фильтров. Использование предложенных подходов позволит комплексно решать ряд вопросов, связанных с выбором параметров батарей конденсаторов в электрических сетях с нелинейными нагрузками. Розроблена методика вибору батарей конденсаторів, які застосовуються як в якості компенсаторів реактивної потужності при наявності джерел інтергармонік, так і в складі фільтрів вищих гармонік і інтергармонік. Отримані
вирази для перевірки відсутності неприпустимих перевантажень батарей конденсаторів по напрузі й по струму при
наявності в кривій напруги (струму), поряд з вищими гармоніками, дискретного спектру інтергармонік. Обґрунтована
доцільність спрощеного врахування зміни напруги на затискачах батарей конденсаторів фільтрів вищих гармонік і
інтергармонік за рахунок наявності реактора в складі фільтрів. Використання запропонованих підходів дозволить
комплексно вирішувати низку питань, пов'язаних з вибором параметрів батарей конденсаторів в електричних мережах з нелінійними навантаженнями Purpose. Development of a methodology for selecting capacitor
bank parameters designed to compensate for reactive power, if there
are sources of interharmonics in the electrical network. Development
of a methodology for selecting the parameters of capacitor banks
that are part of resonant filters of higher harmonics and interharmonics. Methodology. For the research, we used the decomposition
of the non-sinusoidal voltage (current) curve into the sum of the
harmonic components with frequencies as multiple of the fundamental frequency - higher harmonics, and not multiple fundamental frequencies - interharmonics. Results. Expressions are obtained for
checking the absence of inadmissible overloads of capacitor banks
by voltage and current in the presence of voltage (current) in the
curve, along with higher harmonics, of the discrete spectrum of interharmonics. When selecting capacitor banks, both for reactive
power compensation and for filter-compensating devices, the necessity of constructing the frequency characteristics of the input and
mutual resistances of the electrical network for analyzing possible
resonant phenomena is confirmed. Originality. The expediency of
simplified calculation of the voltage variation at the terminals of the
banks of the capacitors of the higher harmonics filters and interharmonics due to the presence of the reactor in the filters is substantiated. Practical value. The use of the proposed approaches will make
it possible to resolve a number of issues related to the choice of parameters of capacitor banks in networks with nonlinear loads, including: ensuring reliable operation of capacitor banks when their
parameters deviate from their nominal values, as well as deviations
in the parameters of the supply network and sources of harmonic
distortion; ensuring the absence of resonant phenomena at frequencies of both higher harmonics and interharmonics